2013
DOI: 10.3233/ves-130490
|View full text |Cite
|
Sign up to set email alerts
|

The development of an accelerometer-based measure of human upright static anterior-posterior postural sway under various sensory conditions: Test–retest reliability, scoring and preliminary validity of the Balance Accelerometry Measure (BAM)

Abstract: Background: Accelerometers are being used to assess postural control in adults, but there is little to support their reliability and validity. Objective: To estimate the test-retest reliability of the balance accelerometry measure (BAM) and to describe the known-groups validity of the BAM composite score. Methods: Two measures of standing postural sway were taken across six sensory (vision/stance surface) and motor stance (feet together or tandem) positions from eighteen patients with vestibular disorders and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 37 publications
11
35
0
Order By: Relevance
“…All 42 subjects completed two balance trials on conditions 1 through 3, like previous reports [13]. Both trials of the eyes closed/foam surface condition (condition 4) were successfully completed by 37 subjects (88%).…”
Section: Smartglasses-based Measurement Of Ap Sway Correlates With Wamentioning
confidence: 53%
See 3 more Smart Citations
“…All 42 subjects completed two balance trials on conditions 1 through 3, like previous reports [13]. Both trials of the eyes closed/foam surface condition (condition 4) were successfully completed by 37 subjects (88%).…”
Section: Smartglasses-based Measurement Of Ap Sway Correlates With Wamentioning
confidence: 53%
“…The first 10 seconds of data were discarded to ensure stability of measures (50 seconds of data total). Accelerometer data (ACC) from each trial was low-pass filtered using a phase less 4th order, Butterworth filter with a cut-off frequency of 1.25 Hz [13]. The normalized path length (NPL; mG/s; higher values indicate more sway) of the acceleration time series from the anterior-posterior (AP) postural sway data was defined as:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These values are shown to be in accordance with values observed in previous and similar studies. Marchetti et al [12] had test-retest reliability of .87 (.68-.95), Merchán-Baeza et al [15] showed intraobserver reliability of .829-.878 and interobserver of .821-.883, and Mellone et al [14] had intraobserver reliability of .72 (.46-.86) and interobserver of .99 (.99-1.00). In the latter study, the reliability was extracted during the execution of a specific section of the TUG test, namely, from sitting to standing [14].…”
Section: Discussionmentioning
confidence: 99%